2019
DOI: 10.1111/tmi.13312
|View full text |Cite
|
Sign up to set email alerts
|

The Vietnamese Version of the Brief Illness Perception Questionnaire and the Beliefs about Medicines Questionnaire: Translation and Cross‐cultural Adaptation

Abstract: objective To translate and cross-culturally adapt the Brief Illness Perception Questionnaire (BIPQ) and the Beliefs about Medicines Questionnaire (BMQ) into Vietnamese.methods We followed the guideline by Beaton et al. (2000Beaton et al. ( & 2007. Stage I: two translators (informed and uninformed) translated the questionnaires. Stage II: the translations were synthesised. Stage III: back translation was performed by two translators fluent in both Vietnamese and English but na€ ıve to the outcome measurement. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Moreover, cross-culturally adaptation was necessary to be conducted. Some adjustments such as how to express plural-singular, as well as countable-uncountable forms, were In line with other studies, one word might be difficult to be interpretated [26], and it was common to replace some words from sentences [27]. It is not easy to get a reliable and valid questionnaire from English to the targeted language by direct translation process [28].…”
Section: Translation and Validationmentioning
confidence: 68%
“…Moreover, cross-culturally adaptation was necessary to be conducted. Some adjustments such as how to express plural-singular, as well as countable-uncountable forms, were In line with other studies, one word might be difficult to be interpretated [26], and it was common to replace some words from sentences [27]. It is not easy to get a reliable and valid questionnaire from English to the targeted language by direct translation process [28].…”
Section: Translation and Validationmentioning
confidence: 68%
“…In addition, the two-factor structure of the Bahasa version of the B-IPQ had acceptable internal consistency estimates with values of Cronbach’s alpha of >0.70, which indicates that the scale has solid reliability and internal consistency. Another key finding of the reliability was that ICC results ranged from 0.82 to 0.90, and the cognitive illness representation had the highest score compared to the emotional domain; these ICC values were higher than values in Malaysia [ 13 ], Korea [ 17 ], and Vietnam [ 40 ], for which score ranges were 0.53~0.78, 0.73~0.86, and 0.44~0.85, respectively. More generally, based on our ICC score and item-total correlation coefficient, we demonstrated that the Bahasa Indonesian version of the B-IPQ is a reliable and stable multidimensional instrument for measuring illness representations, including cognitive illness and emotional representations in Indonesians with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for multifaceted cooperation of administrative authorities, healthcare providers as well as local residents to improve daily practices of pharmacy personnel. [28][29][30] When it comes to medical consultant recommendations, the number of pharmacists recommending a doctor visit was notably low. They failed to meet the requirements to manage childhood seasonal influenza and watery diarrhea inside the local community.…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need for multifaceted cooperation of administrative authorities, healthcare providers as well as local residents to improve daily practices of pharmacy personnel. 28 30 …”
Section: Discussionmentioning
confidence: 99%